ROLE OF ETHNIC IN PRESENT DAY POLITICS WITH SPECIAL REFERENCE TO AHOM MOVEMENT FOR TRIBAL STATUS - Aparna Chutia, (International Journal of Innovations in Engineering Research and Technology, 2015)
Science independence different ethnic groups of North –East started their ethnic movement to assert their ethnic identity in different ways with definite aims and aspirations. As a result of it, some definite ethnic groups of different came into existence. Their seems to be no contention amongst the different ethnic within the states itself. Specially in Assam, it is experiencing such harsh result on contention. Still non- tribals like ahom, Chutia, Konch etc have been demanding to get the Schedule Tribes Status within the sixth schedule of the constitution which is the significant step for gaining political autonomy.The Ahom as distinct ethnic groups of Assam are organizing themselves through their organization in different levels in Assam. The ahom along with other five ethnic groups in assam have been launching movement in different times. Infect, when the Ahom increasingly felt that they remained much more backward than other reactions of the state then they organizing a sound footing body for their development. Basically they have for getting paid attention to include the ahoms in to the scheduled Tribes of the Indian constitution on the basis of their socio-economics backwardness. In view of this, the issue had gained considerable importance in present day politics and would made to analyze the different phases of movement for tribal status of Ahom.